IMPLEMENTASI TERAPI AIUEO DENGAN GANGGUAN AFASIA MOTORIK PADA PASIEN STROKE DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Tajri Arrizqa Br Barus; Erita Gustina; Huwaina Af’idah (SINERGI : Jurnal Riset Ilmiah, 2026)
Stroke is a clinical syndrome characterized by focal or global cerebral dysfunction lasting for 24 hours or more, which may lead to disability or death and is caused by spontaneous bleeding or inadequate blood supply to brain tissue. Motor aphasia is a condition involving damage to the entire cortex in the Broca's area. Motor aphasia manifests as verbal impairment accompanied by symptoms such as difficulty speaking, dysarthria, and visible increased effort when attempting to communicate. The AIUEO therapy is a treatment designed to improve speech so that it can be better understood by others by moving the tongue, lips, facial muscles, and pronouncing the sounds "AIUEO". The "AIUEO" therapy represents a standard pattern of phonetic symbols; thus, when pronouncing "AIUEO", the tongue, lips, and facial muscles move and facilitate speech recovery. The design of this study was descriptive with a case study approach involving two clients diagnosed with the same condition. Nursing interventions were provided by the researcher for three days for both cases with daily evaluations. Nursing actions performed over three days in cases 1 and 2 showed similar outcomes. In case 1, involving aphasia, Mrs. A's initial communication ability improved from a score of 9 to 15, while Mrs. D's score improved from 12 to 16. This speech therapy is administered to individuals experiencing communication disorders. Conclusion and suggestion: the implementation of nursing interventions over three days in both cases demonstrated consistent evaluation results. Clients are advised to perform the therapy regularly in order to achieve optimal outcomes.